Analisis Minat Beli Pelanggan Melalui Sistem Penjualan Cash on Delivery Study Kasus Butik Kemazena di Kabupaten Mamuju - Ratna, Ratna; Juniarni, Selvi; Afriany, Annisa Nur (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2022)
This research takes the title Analysis of Customer Purchase Interest Through Cash On Delivery Sales System Case Study of Kemazena Boutique in Mamuju Regency. The purpose of the research is to find out how the customer's buying interest is in the cash on delivery sales system at the Kemazena Boutique, Mamuju Regency and to find out the implementation of the cash on delivery online sales system at the Kemazena boutique, Mamuju Regency. The results showed that the customer's buying interest in the cash on delivery system at the kamazena boutique, Mamuju Regency, that the average boutique consumer showed interest in buying after knowing the boutique implemented a cash on delivery system, this was marked by the high enthusiasm of consumers who wanted to shop at the boutique without must go directly to the place. And the implementation of an online cash on delivery system at the Kemazena boutique is able to meet consumer expectations by providing solutions to several problems that occur, boutique owners are able to provide trust which has been a factor of doubt over the online shopping experience on the internet, such as cases of rampant fraud. This is happening now. With the presence of a cash on delivery system, it is easier for consumers at Kemazena boutiques and it has an impact on profits for the seller or boutique owner.